Links between ocean properties, ice cover, and plankton dynamics on interannual time scales in the Canadian Arctic Archipelago. Issue 10 (22nd October 2013) - Hamilton, James M.; Collins, Kate; Prinsenberg, Simon J.
Abstract : [1] A decade of instrumented mooring data from Barrow Strait in the eastern Canadian Arctic Archipelago reveals connections between sea ice, water characteristics, and zooplankton dynamics on interannual time scales. On the North side of the Strait, the timing of breakup is positively related to the timing of freezeup in the previous year and negatively related to spring water temperature. This suggests that an early freezeup insulates the ocean from a cold autumn atmosphere, allowing heat to be retained until spring when it contributes to early sea ice erosion. There is also a very strong negative association between the timing of freezeup and late summer salinity, suggesting that monitoring of salinity in real time could be used to predict freezeup. A zooplankton biomass index derived from acoustic Doppler current profiler echo intensity data is used to demonstrate that on the North side there are also strong connections between early summer water temperature and the start, length, and productivity of the zooplankton growth season. On the South side of the Strait where currents are stronger, the relationships seen on the North side were not observed. But here integrated zooplankton biomass index and measured currents are used to identify interannual variability in the zooplankton biomass being delivered downstream into Lancaster Sound. Also on the South side, two yearlong records of daily fluorescence profiles reveal a large difference in the phytoplankton biomass being delivered downstream between years and demonstrate a strong relationship between the timing of the spring phytoplankton bloom and that of breakup. Key Points: Sea ice freezeup and breakup are linked to water column temperature and salinity A zooplankton biomass index is derived from moored ADCP backscatter data Key features of the zooplankton growth season are linked to water temperature